HBR's 10 must reads on performance management. (HBR's 10 must reads (Series), 2023)
"For decades, performance management has been seen as an annual chore by managers and HR alike. But this process is changing, and there are ways to make it more effective for your organization and more useful for employees. If you read nothing else on performance management in your organization, read these 10 articles. We've combed through hundreds of Harvard Business Review articles and selected the most important ones to help you assess performance more accurately, have more-effective feedback conversations, and encourage the growth of your employees. This book will inspire you to learn where current performance management processes are falling short; create sustainable performance across the organization; deliver feedback that motivates and develops your team members; help your people reach their professional goals; identify your role in an employee's poor performance; and evaluate performance fairly, even in a remote environment"--